2014
DOI: 10.1007/s00586-014-3526-1
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomographic morphometric analysis of cervical pedicles in a multi-ethnic Asian population and relevance to subaxial cervical pedicle screw fixation

Abstract: Transpedicular screw fixation is generally feasible in our population except for 8 % with at least one PW < 4.00 mm. However, in view of significant sex and ethnic morphometric variability, pre-operative CT evaluation together with image-guided screw placement is highly advised to ensure safety and accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 23 publications
7
27
0
Order By: Relevance
“…15,16 Various studies have shown a difference between the size of the cervical pedicles in the Western and Asian population. 10,11 Our results demonstrate that anatomical morphometric features of the Graph 5: Mean PW in study subjects cervical pedicles of the studied population are similar to previously reported data but there is a small difference. The majority of existing studies on cervical pedicle measurement relied on the assessment of symptomatic subjects, whereas we assessed cervical pedicle dimensions in asymptomatic subjects.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…15,16 Various studies have shown a difference between the size of the cervical pedicles in the Western and Asian population. 10,11 Our results demonstrate that anatomical morphometric features of the Graph 5: Mean PW in study subjects cervical pedicles of the studied population are similar to previously reported data but there is a small difference. The majority of existing studies on cervical pedicle measurement relied on the assessment of symptomatic subjects, whereas we assessed cervical pedicle dimensions in asymptomatic subjects.…”
Section: Discussionsupporting
confidence: 89%
“…3 Various biomechanical studies have shown that cervical pedicle screw has a better pullout strength than other posterior cervical fixation techniques and failure rate is significantly low. [4][5][6][7] The cervical pedicle surgical anatomy has been studied in North America, Asia, and Europe, [8][9][10][11][12] and it has anatomical parameters of the cervical spine pedicles that may differ in various regions. Indian population have been studied for cervical pedicle morphometry 13,14 but there are no studies about South Indian population without any cervical spine pathology.…”
Section: 2mentioning
confidence: 99%
“…The majority of existing studies on cervical transpedicular screw fixation relied on the assessment of a limited number of patients when compared to our study. [14,15,17] To the best of our knowledge, this is the first time that cervical pedicle dimensions of a Latin American population are measured and analyzed regarding gender and spinal level.…”
Section: Discussionmentioning
confidence: 99%
“…As many other morphometric anatomical differences found in different races and ethnicities, [13,14,18] we believe that data extracted from previous studies should be used with caution because they might not apply universally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation